Analisis Faktor-Faktor Yang Berhubungan Dengan Tingkat Konsumsi Telur Ayam Pada Siswa SD Di Kecamatan Kramat Tegal - Sulistiyono, Irfan; Nuskhi, Muhammad; Purwaningsih, Hermin (ANGON: Journal of Animal Science and Technology, 2019)
Backgrounds. "Analysis of Factors Associated with Chicken Egg Consumption Levels in Elementary Students in Kramat Subdistrict, Tegal Regency" was held on July 17, 2018 - August 1 2018. This study aims to: 1) Know the factors (preference or taste, parents income, parents knowledge of nutrition, and information access to parents amongs elementary students in Kramat Subdistrict, Tegal, and 2) analyse association between preference or taste, parents income, parents knowledge of nutrition, and information access to parents with chicken egg consumption levels amongs elementary students in Kramat Subdistrict, Tegal. Materials and Methodes. This study using a survey method and targeting 6th grade elementary school students who consumed chicken eggs in Kramat Tegal Subdistrict. Study was conducted in 3 selected elementary schools (Maribaya 01 Elementary School, Munjung Agung Elementary School, and West Mejasem Elementary School 03) using Stratified Random Sampling method. Sampling was using purposive sampling method in Kramat District, Tegal. The analysis of this study using Spearman Rank correlation analysis. Results. The results showed that the preference or taste variables included in the high category, the variable parents knowledge of nutrition and the access information variables of parents in the medium category, and the variable income of parents is low category. Conclusions. The results of the Rank Spearman correlation analysis showed that the preference or taste variables and parents income were positively related to the level of consumption of chicken eggs, while the variable knowledge of parental nutrition and access to parental information were not significantly related to the level of consumption of chicken eggs in elementary students in Kramat Subdistrict, Tegal.